2018
DOI: 10.3390/toxins10080336
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Toad Toxins as Potential Therapeutic Agents

Abstract: Toxins from toads have long been known to contain rich chemicals with great pharmaceutical potential. Recent studies have shown more than 100 such chemical components, including peptides, steroids, indole alkaloids, bufogargarizanines, organic acids, and others, in the parotoid and skins gland secretions from different species of toads. In traditional Chinese medicine (TCM), processed toad toxins have been used for treating various diseases for hundreds of years. Modern studies, including both experimental and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 71 publications
0
62
0
Order By: Relevance
“…Previous studies have also reported these uses in other Latin American countries [62][63][64] and other regions of the world [65,66]. Besides, in recent decades there has been increasing evidence on the possibility of pharmacological synthesis based on chemical components obtained from secretions, tissue, and venom extracted from amphibians and reptiles [67][68][69][70], which shows the correspondence between the use of species in the traditional culture, as well as in current and future applications in medicine.…”
Section: Use and Cultural Beliefsmentioning
confidence: 99%
“…Previous studies have also reported these uses in other Latin American countries [62][63][64] and other regions of the world [65,66]. Besides, in recent decades there has been increasing evidence on the possibility of pharmacological synthesis based on chemical components obtained from secretions, tissue, and venom extracted from amphibians and reptiles [67][68][69][70], which shows the correspondence between the use of species in the traditional culture, as well as in current and future applications in medicine.…”
Section: Use and Cultural Beliefsmentioning
confidence: 99%
“…All screened compounds were input into the PubChem database, whereas compounds with duplicated data and without structural information were removed. We obtained the canonical Simplified Molecular Input Line Entry Specification (SMILES) and structural information of 23 compounds [7,[11][12][13]. e specific results are shown in Table S1.…”
Section: Compounds Of Cinobufotalin Injectionmentioning
confidence: 99%
“…Cinobufotalin injection, a water-soluble preparation extracted from Chinese giant salamander or black sable, has been approved by the China Food and Drug Administration (ISO9002) for the treatment of malignant tumors [6,7]. Jiang et al [8] carried out maintenance therapy in 64 patients with NSCLC who did not progress after first-line chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Brazil is the country with the richest biodiversity of anuran amphibians, with 1093 catalogued species, of which at least 42 are on the list of endangered species [ 1 , 2 , 3 ]. Of particular interest are the biological activities of anuran gland and skin secretions, not only because of their physiological, behavioral, and ecological functions, but also because their complex composition provides a rich source of novel chemicals with potential biotechnological and therapeutic applications [ 4 , 5 , 6 , 7 , 8 ]. In addition, many anurans (and amphibians in general) have complex mechanisms to avoid diseases, parasites, and predation that frequently involve the use of a variety of secretions, the composition of which may be modulated by environmental factors [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%